(untitled) (Economic and Political Thought, 2010)
The author of the article discusses the issue of energy security starting with a characteristic comment on Sascha Muller-Kraenner’s book titled “Energy Security – re-measuring the world”, going through a presentation of selected European Union plans, ideas and activities in that respect and finally presenting and examining a new Jerzy Buzek’s and Jacques Delors’ idea to create European Energy Community. The article discusses issues connected with dual mutually dependent complex of threats growing on the security axis, i.e. energy industry and ecology. There is also an analysis of the necessity to develop a common energy strategy and the issue of the present domination of particular interests of the member states which can have a highly destructive effect on the idea of the European integration. Preparing the article, the author drew on his analysis of documents and current European Union and member states’ actions. The conclusions draw readers’ attention to fears about a really common form of action of the member states due to their varied approach towards the issue and inability to develop a really common energy policy. The deliberations led the author to a conclusion that the same sectoral integration that started the process of European Union creation in the 1950s can be the beginning of its end.